PRACTICAL IMPORTANCE OF SURGICAL TREATMENT OF LOCALLY ADVANCED STOMACH CANCER - Yulchiyev Karimjon,,; Haydarov Abdulhamid , (TADQIQOTLAR.UZ, 2024)
Currently, aggressive surgical tactics are becoming more and more distinct, the proponents of which advocate the most complete removal of a stomach tumor in a locally widespread process. However, this approach is not shared by all surgeons. Indications forcombined resections and palliative interventions remain contradictory. The results of surgical treatment of locally advanced gastric cancer cannot be considered satisfactory. There is a fairly frequent (38-60%) refusal of surgical treatment due to the prevalence of the tumor process. Even after potentially radical operations, most patients with locally advanced gastric cancer die from tumor progression and recurrence. The lack of a single surgical tactic, the inconsistency of immediate and long-term treatment results determined the relevance of this study.